Anatomical Study of the Grasscutter’s Aorta (Thryonomys swinderianus, Temminck 1827) - Sogan, Ananivi; Broalet, Maman You Esperance; Hounake, Mawunyo Afanvi; James, Yaovi Edem; Agbonon, Amegnona; Hounnou, Martial Gervais (European Scientific Journal, ESJ, 2026)
Introduction: The largest artery in the body, from which practically all other arteries originate, knowledge of the anatomy of the grasscutter’s aorta, an anatomical model, is important. Aim: We aim to describe the grasscutter’s aorta and identify its main branches. Materials and methods: This was a morphological, cross-sectional, and descriptive study of the aortas of five large grasscutter species. Final killing was performed by exsanguination from the left ventricle after a thoraco-abdominal part under general anesthesia. Aorta dissections were performed on fresh grasscutter species and after vascular injection of colored latex. The parameters studied were the origin, route-termination, main branches, and the length and diameters of the aorta. Results: The aorta originated at the base of the left ventricle and terminated at the entrance to the pelvic cavity after an initial course describing an arch and then a nearly medial thoracic and abdominal segment in the cranio-caudal direction. The main branches were two coronary arteries, two supra-aortic trunks, a constant celiac trunk, either one mesenteric artery or two mesenteric arteries. The average length of the aorta was 132.48 mm with average diameters of 1.60 mm; 1.46 mm and 1.04 mm respectively at the ascending aorta, the descending thoracic aorta, and the abdominal aorta. Conclusion: The grasscutter’s aorta qualitatively presents the same main branches as that of humans.